Case report: Bullous pemphigoid combined with Sjögren’s syndrome complicated by central nervous system infection - Chen, Xing-Yue; Chen, Jun; Long, Kun-Lan; Ding, Peng; Li, Rong; Zhi, Li-Jia (Frontiers in Immunology, 2024)
Background: Bullous pemphigoid (BP) is the most common autoimmune blistering skin disease in humans, characterized by tense blisters, erosions, urticarial lesions, and itching on normal or erythematous skin. Many autoimmune diseases are considered comorbidities of BP, but clinical case reports of BP complicated by Sjögren's syndrome are very scarce. Furthermore, cases of central nervous system infection secondary to both autoimmune diseases are even rarer. Case presentation: we report a 74-year-old woman diagnosed with bullous pemphigoid, who showed relief of active lesions after treatment with methylprednisolone and dupilumab injections. However, she was admitted for pulmonary infection during which she was diagnosed with Sjögren's syndrome (SS). Subsequently, the patient developed altered consciousness, indicating a central nervous system infection. Adjustment of steroid dosage and aggressive antimicrobial therapy led to alleviation of symptoms.The coexistence of autoimmune subepidermal blistering diseases and SS is rare. The role of SS in the pathogenesis of skin lesions is unclear, and the relationship between these blistering diseases and SS remains elusive. Further research is needed to determine whether there are common pathological mechanisms between the two conditions. 【Keywords】 Bullous pemphigoid; Sjogren's syndrome; Pathological mechanisms; Autoimmune diseases; Central nervous system infection 【Introduction】 Bullous pemphigoid (BP) is the most common autoimmune blistering disease, primarily affecting the elderly, with peak onset around 80 years of age, and no significant gender difference [1]. Clinical manifestations mainly include erythematous urticarial plaques, blisters, and intense itching. It is induced by autoantibodies against two dermal-epidermal junction proteins, BP180 and BP230. Binding of autoantibodies leads to complement activation, inflammatory reactions, degranulation of mast cells, accumulation of neutrophils and eosinophils, and release of proteases cleaving BP180, resulting in blister formation [2]. The pathogenesis of BP is largely unknown, but previous cases have been associated with specific "potential triggers" such as drugs [3][4], physical factors, vaccines[5], infections, and transplants. The gold standard for BP